Analysis of the Influence of Green Trust, Green Marketing and Green Perceived Quality on Green Purchase Intentions on Consumers of Aqua Brand Bottled Water with 100% Recycled - Andri Wibowo; Wiwik Prihartanti; Agung Edy Wibowo; Hardiono; Agus Rahmato (Enrichment : Journal of Management, 2022)
This study aims to determine and explain the effect of green trust, green marketing and green perceived quality on green purchase intention. The type of research used is explanatory with a quantitative approach. The population in this study were students of the Faculty of Economics & Business and the Faculty of Social and Political Sciences Semester VII and were still active at W.R. Supratman University in Surabaya. The sample used in this study was 71 respondents who were taken using purposive sampling and data collection methods using questionnaires or online questionnaires. Data analysis used is descriptive statistical analysis and multiple linear regression analysis. The data in this study were processed using SPSS 23 for Windows. The results of this study indicate that green trust, green marketing and green perceived quality partially affect the green purchase intention of mineral water in Aqua packaging.